A review of the concept of «accumulation by dispossession” of D. Harvey - Gil Sánchez, Fernando (Anales del Seminario de Historia de la Filosofía, 2019)
The objective of this article will be to make a critical review of the interpretation made by D. Harvey of the concept of «original accumulation» exposed by K. Marx in Capital. Trough the analysis of the writings where Marx approaches this question, we will try to show that the main contribution of Harvey –to reinterpret the original accumulation, not as a foundational process of the necessary conditions for capitalist production, not as a continuous and permanent process used to restore the optimal conditions of the accumulation of capital through the conquest of new spaces- is based on a partial interpretation of the Marxian political economy’s critical texts that confuse the logical and historical dimension of Marxian analysis. So that, we will argue that there is a basis in Marx’s own texts from which to interpret «original accumulation» as a process of constant dispossession in the development of the capitalist mode of production that, dependent on constant expansion, enhances its adaptive capacity through the conquest of those factors of the economy not yet incorporated into the process of capital.
Keywords: Original Accumulation; Accumulation by dispossession; Capital; Counteracting causes; Law of the declining trend of the rate of profit